A strategy to flexibly operate a solar aided power generation plant for wide irradiation conditions. (August 2022) - Qin, Jiyun; Zhang, Qinglei; Liu, Zhen; Hu, Eric; Zhang, Hongsheng
Highlights: A novel flexible solar replacement strategy has been proposed. The novel strategy is suitable for wide range irradiation conditions. The novel strategy can efficiently use non-ideal solar radiation. Adopting novel strategy can promote annual solar contribution. Abstract: Solar Aided Power Generation is a solar thermal hybrid power system, in which solar heat is used to replace the heat of extraction steam for a Rankine cycle power plant by preheating the power plant feedwater to boiler. In this power system, low to high temperature solar heat can flexibly replace extraction steam at different stages, the most common replacement strategy is medium to high temperature solar heat used to replace extraction steam to all high-pressure stages. However, this solar replacement strategy faces a problem of inefficient utilisation of non-ideal solar irradiation, which limits the annual solar contribution of the hybrid power system. In the present study, a novel solar replacement strategy, which can efficiently use wide range solar irradiation, is proposed. In this strategy, the extraction steam replacement stages can be flexibly selected depending on the solar radiation condition. In this study, the performance of a power system for the novel strategy and most common replacement strategy (i.e., solar heat used to replace extraction steam to all high-pressure stages) have been compared based on a hybrid power system modified from 300 MW power plant. The results indicate that the solar contribution of the power system operated with novel strategy can be improved by 6.6% and 11.9% for typical winter and summer days, respectively. Also, by using the novel strategy, the annual solar contribution and annual solar operation hours can be improved by 6.7% and 1488 h.